Teacher Educators' Application of Learning from Technology Professional Development - Foster Gondwe; Frank Mtemang'ombe; Chikumbutso Manthalu (University of Johannesburg, 2023)
This study explored teacher educators' application of learning from technology professional development (TPD). Participants were drawn from a teacher training college and a Non-Governmental Organization (NGO) implementing an educational technology programme. The NGO case served as a snapshot to draw lessons that might be useful for teacher educators' TPD in public teacher education institutions. The findings showed that while teacher educators confirmed their application of learning through student teachers' performance, they reported work environment conditions and individual characteristics as obstacles to application of learning. The findings point to individual motivation, needs and obstacles concerning teacher educators' TPD in Malawi.